Generation of pure endothelial cells from transgenic embryonic stem cells exhibiting an endothelial cell-specific expression of green fluorescent protein upon differentiation - Raissi Dehkordi, Maria; Justus Liebig University Giessen (My University, 2015)
Embryonic stem (ES) cell-derived endothelial cells (EC)s may be used as a therapeutic option in experimental models of diseases originating from vascular lesions. Moreover, studies on these cells may provide insight into EC development and differentiation in the human body. In this regard, it is fundamentally required to label, track, and finally isolate a pure population of ES-cell-derived ECs. In this study, a murine ES cell line was established, which expressed green fluorescent protein (GFP) as well as a zeocin resistance gene under the control of the murine Vascular Endothelial (VE)-cadherin promoter after lentiviral transduction of single ES cells. 192 ES colonies derived from single transduced ES cells were picked randomly and directed to differentiation. From day 6 of differentiation, 12.5% of the clones showed GFP-positive vessel-like structures. Immunofluorescence microscopy demonstrated the co-expression of various EC markers (VE-cadherin, CD31) on ES cell-derived vascular structures. Based on flow cytometry, the highest GFP expression level could be observed in embryoid bodies at differentiation day 8. Flow-cytometric cell sorting at this time point revealed a significantly higher level of expression of the majority of investigated EC markers in the GFP-positive compared to the GFP-negative population. In addition, magnetic beads were used for the isolation of ECs based on CD31 expression. The sorted cells were subsequently subjected to gene profiling, in order to determine the optimal time point for the isolation and subsequent culture of ECs. In the sorted cells on days 6 and 8 of differentiation, all investigated markers of EC differentiation and transcription factors of vasculogenesis demonstrated a markedly higher expression in the CD31-positive versus CD31-negative population. Cultured CD31-positive cells at differentiation day 6 developed a characteristic EC cobblestone morphology, co-expressed GFP and different endothelial markers, and eventually formed tube-like structures. In conclusion, generation of ES cell clones expressing GFP upon differentiation to ECs, and their sorting based on CD31, provides a feasible method for the production of pure labeled ECs. This system may serve as a powerful tool for studies on the differentiation of ECs from ES cells and induced pluripotent stem cells, as well as prospective cellular therapeutic approaches in various diseases associated with vascular damage.

Aus embryonalen Stammzellen (ES-Zellen) abgeleitete Endothelzellen können in Modellen zur Therapie von Erkrankungen, die mit vaskulären Läsionen assoziiert sind, eingesetzt werden. Außerdem geben ES Zellstudien wichtige Einblicke in die Entwicklung und Differenzierung von Endothelzellen im menschlichen Organismus. Für diese Zwecke ist es essentiell, die aus ES-Zellen abgeleiteten Endothelzellen zu markieren und nachzuverfolgen und die differenzierten Zellen schließlich in eine reine Zellpopulation zu überführen. In der vorliegenden Arbeit wurde eine murine ES-Zell-Linie generiert, welche nach lentivirusbasierter Transduktion von ES Zellen das grün fluoreszierende Protein (GFP) sowie ein Zeocin-Resistenzgen unter Kontrolle des murinen vaskulären endothelialen (VE)-Cadherin-Promotors exprimiert. 192 aus einzel-transduzierten ES-Zellen abstammende ES-Zellkolonien wurden zufällig selektiert. Ab Tag 6 der Differenzierung zeigten 12,5% der Klone GFP-positive vaskuläre Strukturen mit Co-Expression verschiedener vaskulärer Marker (VE-Cadherin, CD31). Die durch Durchflusszytometrie am Tag 8 der Differenzierung selektierten GFP-positiven Zellen zeigten eine signifikant höhere Genexpression verschiedener Endothelzellmarker als die GFP-negative Zellpopulation. Darüber hinaus wurde ein weiteres, auf der Expression von CD31 basierendes Verfahren zur Selektion der aus ES Zellen abgeleiteten Endothelzellen angewendet und das Genprofil der selektierten Endothelzellen zu verschiedenen Zeitpunkten der Differenzierung analysiert. Auf diese Weise wurde der optimale Zeitpunkt für die Isolierung und anschließende Kultivierung und Charakterisierung dieser Zellen festgelegt. Alle untersuchten Marker sowie Transkriptionsfaktoren der Endotheldifferenzierung zeigten eine deutlich höhere Expression in der CD31-positiven gegenüber der -negativen Zellpopulation am Tag 6 und 8 der Differenzierung. Die Kultivierung der CD31- positiven Zellen am Tag 6 der Differenzierung führte zu einer für Endothelzellen charakteristischen Kopfsteinpflastermorphologie mit Co-Expression des GFPs mit verschiedenen endothelialen Markern. Schließlich bildeten die kultivierte Zellen tubuläre Strukturen aus. Zusammenfassend stellt die Generierung embryonaler Stammzellklone, welche während der Differenzierung zu Endothelzellen GFP exprimieren, und die Selektion dieser Zellen auf Basis der Expression von CD31, eine effiziente Methode für die Entwicklung reiner Endothelzellen dar. Diese Studien repräsentieren darüber hinaus die Voraussetzung für zukünftige detaillierte Studien zur Differenzierung von Endothelzellen aus ES Zellen und induzierten pluripotenten Stammzellen, und für die Anwendung Zell-basierter experimenteller therapeutischer Strategien bei verschiedenen vaskulären Erkrankungen.
Keywords: ddc:610